2017
DOI: 10.1155/2017/4168541
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nutritional Deficiencies and Small-for-Gestational-Age Neonates at Birth of Women Who Have Undergone Bariatric Surgery

Abstract: The aim is to compare the prevalence of maternal deficiencies in micronutrients, the obstetrical and neonatal complications after bariatric surgery according to surgical techniques, the time between surgery and conception, and BMI at the onset of pregnancy. A retrospective cohort study concerned 57 singleton pregnancies between 2011 and 2016 of 48 adult women who have undergone bariatric surgery. Small-for-gestational-age neonates were identified in 36.0% of pregnancies. With supplements intake (periconception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Norgaard et al found no difference in the prevalence of SGA prior to, or after, 18 months (level 2++). Other studies also did not find a difference in gestational outcomes according to surgery to conception interval …”
Section: Evidence and Recommendationsmentioning
confidence: 86%
“…Norgaard et al found no difference in the prevalence of SGA prior to, or after, 18 months (level 2++). Other studies also did not find a difference in gestational outcomes according to surgery to conception interval …”
Section: Evidence and Recommendationsmentioning
confidence: 86%
“…Vitamin A deficiency was reported in 10% to 58% of pregnant women after BS, depending on BS procedure and gestational age [51, 61, 85]. Vitamin A, alone or in combination with other fat-soluble vitamins (D, E, K), has to be supplied if deficiencies are present [60, 61].…”
Section: Challenges and Benefits Of Bariatric Surgery Before Pregnancymentioning
confidence: 99%
“…In several studies and case reports, evidence could be found that after bariatric surgery women who become pregnant suffer from micronutrient deficiencies, e.g., vitamins A, D, C, B1, and B9 and selenium [74][75][76][77][78]. Furthermore, a study submitted that intake of proteins and omega 3 fatty acids could be difficult [77].…”
Section: Pregnancy and Breastfeedingmentioning
confidence: 99%
“…This underlines the importance of screening for any deficiency and, especially for pregnant or breastfeeding patients, the long-term intake of nutritional supplements like vitamins, minerals, and trace elements [74,76,78,82,83]. By not doing this, severe complications for mother and child could arise [76].…”
Section: Pregnancy and Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation